Mosquitocidal potential and chemical composition of essential oil and ethanolic extract of litsea petiolata Hook.F. (lauraceae) from Northern Thailand against aedes aegypti (Diptera: Culicidae) - Roongtawan Muangmoon (2019)
© 2019, SEAMEO TROPMED Network. All rights reserved. In an on-going process of screening for insecticides derived from Thai medicinal plants, extracts of Litsea petiolata (“Thummang” in Thai) leaves demonstrated promising larvicidal activity against Aedes aegypti, a dengue vector. Qualitative analysis of chemical composition using gas chromatography coupled with mass spectrometry revealed that principal constituents present in L. petiolata leaf essential oil (EO) were 7-octen-2-one (44.19%) and 2-undecanone (23.29%), together with (Z,E)-farnesol (8.52%), β-caryophyllene (7.46%) and 12-tridecen-2-one (4.85%); while those of ethanol extract (EE) were 7-octen-2-one (23.22%), bis (2-ethylhexyl) phthalate (20.92%) and 2-undecanone (11.50%), together with 12-tridecen-2-one (9.32%), α-tocopherol (8.16%) and propylparaben (6.82%). After a 24-hour treatment period, EO and EE demonstrated a 50% lethal dose against Ae. aegypti larvae of 27.7 and 188 mg/l, respectively and against adult stage of 2.40 and 10 µg/mg female mosquito, respectively. EO provided 100% repellent protection for 15 minutes against Ae. aegypti but EE showed no repellent activity. This study provides data favorable for developing essential oil from L. petiolata leaves as an alternative or supplementary natural product insecticide for inclusion in a mosquito control management program.